Isolation and fermentative activity of rumen anaerobic fungi in dairy cows (Revista de Ciências Agroveterinárias, 2015)
The possibility of biotechnological application of anaerobic fungi and their biomass-degrading enzymes has been a growing area of research and development over the past decade. In this context, the occurrence and isolation of rumen fungi were evaluated in three Holstein-Gir dairy cows grazing Urochloa spp., in addition to the fermentation capacity of theses isolates in media containing different carbohydrates. Motile zoospores were found in all of the rumen samples. Twelve fungal strains were recovered and were capable of degrading different carbohydrates and lignocellulosic components, suggesting that these strains are able to produce various degradative enzymes when grown on glucose, xylose, cellobiose, fructose, and cellulose. Results pointed out the first insight into the isolation of rumen anaerobic fungi in dairy cattle in Brazil and suggested that further studies are needed to show the potential of some species for commercial application, especially in tropical ruminants.
Keywords: Chytridiomycetes; rumen microbiology; dairy cattle; tropical forage.